Incorporation of Three Endocytosed Varicella-Zoster Virus Glycoproteins, gE, gH, and gB, into the Virion Envelope - Maresova, Lucie (American Society for Microbiology, 2005)
The cytoplasmic tails of all three major varicella-zoster virus (VZV) glycoproteins, gE, gH, and gB, harbor functional tyrosine-based endocytosis motifs that mediate internalization. The aim of the present study was to examine whether endocytosis from the plasma membrane is a cellular route by which VZV glycoproteins are delivered to the final envelopment compartment. In this study, we demonstrated that internalization of the glycoproteins occurred in the first 24 h postinfection but was reduced later in infection. Using surface biotinylation of VZV-infected cells followed by a glutathione cleavage assay, we showed that endocytosis was independent of antibody binding to gE, gH, and gB. Subsequently, with this assay, we demonstrated that biotinylated gE, gH, and gB retrieved from the cell surface were incorporated into nascent virus particles isolated after density gradient sedimentation. To confirm and extend this finding, we repeated the above sedimentation step and specifically detected envelopes decorated with Streptavidin-conjugated gold beads on a majority of complete virions through examination by transmission electron microscopy. In addition, a gE-gI complex and a gE-gH complex were found on the virions. Therefore, the above studies established that VZV subsumed a postendocytosis trafficking pathway as one mechanism by which to deliver viral glycoproteins to the site of virion assembly in the cytoplasm. Furthermore, since a recombinant VZV genome lacking only endocytosis-competent gE cannot replicate, these results supported the conclusion that the endocytosis-envelopment pathway is an essential component of the VZV life cycle.